An alternative in small business finance: Community-based factoring companies and small business lending - Dimitri B. Papadimitriou; Ronnie J. Phillips; L. Randall Wray (Levy Economics Institute of Bard College, 1994)
At a time when small businesses are suffering from a credit crunch, 'niche' financial institutions are filling the void left by more traditional sources of financing, such as commercial banks. The authors argue that the most important of these niche players are community-based factor companies, which are rapidly expanding from their client base in apparel and textiles to finance a range of firms in everything from electronics to health care. The purchase of accounts receivable by factors enhances the balance sheets of their clients, making it easier for the clients to obtain bank financing. Also, because factors are more interested in the creditworthiness of a client's customers than of the client itself, they are willing to extend loans in excess of collateral to rapidly growing businesses. Because factors are becoming an increasingly important source of financing for small and start-up businesses, the authors propose that factors be encouraged to play a broader role in financing firms in distressed communities by (1) making some factors eligible for funding and assistance under legislation regulating community development financial institutions and (2) by allowing investments by banks in factors to count toward compliance under the Community Reinvestment Act.
Keywords: 330